Institutes conserving crop germplasm: The IBPGR (International Board for Plant Genetic Resources) global network of genebanks - Hanson, J.; Williams, J.T.; Freund, R.; International Board for Plant Genetic Resources (1984)
Information is presented (1) on base collections of seed samples (i.e. seeds stored for long periods with low moisture contents and at low temperatures) and active collections (from which seeds are obtained for distribution, evaluation and multiplication); (2) the operation of the IBPGR [International Board for Plant Genetic Resources, Rome, Italy] global network of base collections; and (3) standards for seed storage, including information on quality, sample size, drying and moisture content and its determination, containers, storage temperature and monitoring viability and regeneration. A list is given by crop of (1) organizations which maintain IBPGR designated security base collections of germplasm of both a global and regional nature and (2) other significant collections stored for the long and medium term. Details of collections in long or medium storage are given by country in a second list, with information on address of organization, major crops maintained and seed storage conditions. A third list gives the names of organizations at which genebanks are under construction or are being upgraded. (Abstract © CAB ABSTRACTS, CAB International)